A cross-sectional study on serum high-sensitivity C-reactive protein level and shift work among reproductive age women - Maryam Nikpour; Aram Tirgar; Behzad Heidari; Abbas Ebadi; Fatemeh Ghaffari; Akram Hosseini (Babol University of Medical Sciences, 2019)
Background: Among the inflammatory factors, high-sensitivity C-reactive protein (hs-CRP) is one of the strongest predictors of cardiovascular disease. This study aimed to evaluate the relationship of serum hs-CRP level with shift work among reproductive age women. Methods: This cross-sectional study was conducted from September 2017 to May 2018 in three cities in Mazandaran Province, North of Iran. Through purposive sampling, 350 women (172 shift workers and 178 day workers) were recruited. The guideline recommended by the American Heart Association and the Centers for Disease Control and Prevention was used to interpret the result of hs-CRP measurement as the following: less than 1 µg/ml: low CVD risk; 1-3 µg/ml: moderate CVD risk; and more than 3 µg/ml: high CVD risk. The data were analyzed using the independent-sample t and the chi-square tests as well as the logistic regression analysis. Results: 11.1% of participants had a serum hs-CRP level of more than 3 µg/ml. This rate among shift workers was significantly greater than day workers (15.6% vs. 7.0%; p=0.012). After adjusting the effects of potential confounders shift work significantly increased the odds of serum hs-CRP level of more than 3 µg/ml by 2.45 times (OR=2.45, 95% CI: 1.01-5.93, p=0.047). Conclusion: Shift work is a significant predictor of high serum hs-CRP level probably due to its association with sleep problems and occupational stress. Improving the knowledge of female shift workers about the importance of quality sleep can reduce their CVD risk and improve their health.